Nutritional composition, descriptive sensory analysis and consumer acceptability of products developed from Agave americana flowers - Semuli, Makamohelo (University of the Free State, 2014)
The nutritional composition of agave flowers was determined and the following nutrients were analysed: moisture (86.62%); energy (226 kJ/100 g); proteins (1.71 g/100 g); fat (0.46 g/100 g); dietary fibre (2.12 g/100 g); K (207.77 mg/100 g); Mg (53.06 mg/100 g); Ca (48.33 mg/100 g); P (32.12 mg/100 g); Na (1.27 mg/100 g); Fe (1.03 mg/100 g); Zn (0.66 mg/100 g); Cu (0.04 mg/100 g); and Mn (0.15 mg/100 g). In contrast to many vegetables, the flower samples contained sugars in the form of sucrose (0.52 g/100 g), glucose (0.77 g/100 g), fructose (1.06 g/100 g) and maltose (0.69 g/100 g). The vitamin C content was 1.03 mg /100 g, but no vitamin A was detected. When compared to other flower vegetables, the agave flower had the lowest contents for protein, P, K, Mn, Na, Cu and vitamin C, but the highest value for fat. The agave flower and artichoke had similar values for energy, moisture and Mg, while the cauliflower and agave compared well in regard to Ca and Zn contents. Broccoli had similar contents for protein, fibre, P and Cu. The agave had higher values for energy, and fat than cauliflower, and higher fat and Ca, Fe, Mg, P and Zn values than broccoli. Artichokes had lower contents for moisture, fat, Ca and Zn than the agave flowers. Broccoli and cauliflower were moister than the agaves. Descriptive sensory analysis was used to investigate how various treatments would influence the sensory properties of Agave americana flowers. Blanched and unblanched flowers, subjected to three treatment methods (steaming, stir frying and pickling), were analyzed by ten trained panelists, in three replications. The data was analyzed using principle component analysis. A lexicon of 20 attributes was generated, including 11 for the steamed treatment, an additional six for the stir fried treatment and another four for the pickled treatment. Of these, three descriptors were for the attribute aroma, six for mouthfeel, five for appearance, four for taste and one for aftertaste. The unblanched pickled agave flowers were characterized by crunchy, fibrous and chewy mouthfeel, bitter taste, green pepper colour and cactus appearance, and a cucumber odour. For the blanched pickled agave flowers, taste descriptors were prominent, namely sweet, sour and sweet-sour, followed by a sweet aftertaste, combined with a moist appearance. For all the unblanched flowers, regardless of treatment, some of the descriptors had negative connections, like fibrous, bitter, cactus and rancid. Descriptors for the blanched flowers, again regardless of treatment, were more favourable and included sweet, sour and sweet-sour taste, and green bean and nutty odour. Three panels of 50 members each participated in the consumer acceptance tests, one each for the steamed breads and chocolate cakes, and one for the stew and deep fried flowers. Apart from acceptability, aroma, taste and texture were also evaluated for the baked products. The breads, cakes and stews were defrosted at 4 ºC overnight. The breads and cakes were left at room temperature (22ºC) before serving, while the stews were served heated. The breads, fritters and stews were prepared with blanched flowers, while the cake was made with unblanched flour. All the products were acceptable, but in different degrees. The scores were lower for aroma and final acceptability of the bread, due to unfamiliar texture experienced by the consumer panel. The agave cake scored lower for aroma and taste, but higher than the bread on texture. The stews and battered agave fritters were liked by the consumer panels and scored between 6.92 and 7.26 on the hedonic scale.

Die nutrientsamestelling van die agaweblomme is bepaal en die volgende voedingstowwe is ontleed: vog (86.62%); energie (226 kJ/100 g); proteïene (1.71 g/100 g); vet (0.46 g/100 g); vesel (2.12 g/100 g); K (207.77 mg/100 g); Mg (53.06 mg/100 g);Ca (48.33 mg/100 g); P (32.12 mg/100 g); Na (1.27 mg/100 g); Fe (1.03 mg/100 g); Zn (0.66 mg/100 g); Cu (0.04 mg/100 g); en Mn (0.15 mg/100 g). In teenstelling met baie groentes, bevat die agaweblomme suiker in die vorm van sukrose (0.52 g/100 g), glukose (0.77 g/100 g), fruktose (1.06 g/100 g) and maltose (0.69 g/100 g). Die vitamien C-inhoud was 1.03 mg /100 g, maar geen vitamien A is bepaal nie. In vergelyking met ander blomgroentes het agaweblomme die laagste proteïen- P-, K-,Mn-, Na-, Cu- en vitamien C-inhoud, maar die hoogste waarde vir vet. Die agaweblom en artisjok het eenderse waardes vir energie, vog en Mg, terwyl blomkool en die agave goed met mekaar vegelyk ten opsigte van Ca- en Zn-inhoud. Brokkoli het dieselfde inhoud as die agaweblom vir proteïene, vesel, P en Cu. Die agawe het hoër energieen vetinhoud as blomkool, en hoër vet- en Ca-, Fe-, Mg-, P- and Zn-inhoud as brokkoli. Artisjokke het laer vog-, vet-, Ca- en Zn-inhoud as die agaweblomme. Brokkoli en blomkool het ‘n hoër voginhoud as die agawes. Beskrywende sensoriese analise is gebruik om te wys hoe verskillende behandelings die sensoriese eienskappe van Agave americana blomme kan beïnvloed. Geblansjeerde en ongeblansjeerde blomme, voorberei met behulp van drie behandelings (stoom, roerbraai en pekeling), is beskryf deur tien opgeleide paneellede. Die data is ontleed met behulp van ‘principle component analysis’. ‘n Woordeskat van 20 kenmerke is opgestel, insluitend 11 beskrywende woorde vir die stoom-behandling, nog ses vir die roerbraai-behandeling en ‘n verdere vier vir die pekelbehandeling. Van hierdie beskrywende woorde was drie vir aroma, ses vir mondgevoel, vyf vir voorkoms, vier vir smaak en een vir nasmaak. Die ongeblansjeerde gepekelde agaweblomme is gekenmerk deur bros, veselagtige en taai mondgevoel, bitter smaak, groensoetrissiekleur, kakatusvoorkoms en ‘n komkommergeur. Vir die geblansjeerde gepekelde agaweblomme was smaak-beskrywers prominent, naamlik soet en soetsuur, gevolg deur ‘n soet nasmaak, gekombineer met ‘n nat voorkoms. Beskrywende woorde vir al die ongeblansjeerde blomme, ongeag behandeling, het negatiewe verbintenisse gehad, soos veselagtig, bitter, kaktus en galsterig. Die beskrywende woorde vir die geblansjeerde blomme was, ongeag van die behandeling, meer gunstig en het soet, suur en soetsuur smaak, en groenboontjie- en neuterige geur ingesluit. Drie panele, van 50 lede elk, het deelgeneem aan die verbruikersaanvaardingtoetse, een elk vir die gestoomde brode en sjokoladekoeke, en een vir die bredies en diepvetgebraaide blomme. Naas aanvaarding, is geur, smaak en tekstuur ook geêvalueer vir die gebakte produkte. Die brode, koeke en bredies is oornag ontdooi by 4 ºC. Die brode en koeke is by kamertemperatuur gehou tot bediening, tewyl die bredies warm bedien en die poffers vars gebraai was. Die brode, poffers en bredies is gemaak van geblansjeerde, meel/blomme, terwyl die koek gemaak is van ongeblansjeerde agawemeel. Al die produkte was aanvaarbaar, maar in verskillende grade. Die waardes vir die geur en finale aanvaarbaarheid van die gestoomde brood was laer as gevolg van die tekstuur wat ongewoon was vir die paneel. Die agawekoek het laer waardes gekry vir aroma en smaak, maar hoër waardes vir tekstuur as die brood. Die verbruikerspaneel het gehou van die bredies en gebraaide agawepoffers, soos duidelik sigbaar uit die tellings van 6.92 en 7.26 op die hedoniese skaal.
Dissertation (M.Sc. (Consumer Science))--University of the Free State, 2014
Keywords: Consumer; Product development; Pickled; Descriptive sensory; Blanching; Nutrient; Agave flower; Agaves